2006
DOI: 10.1063/1.2358683
|View full text |Cite
|
Sign up to set email alerts
|

Remote bond breaking by interacting temporary anion states

Abstract: The cross section for bond breaking at the site of a dissociative temporary negative ion state through the dissociative electron attachment process can be considerably enhanced by the presence of a second longer-lived temporary negative ion state elsewhere in the molecule, even one quite remote from the first. In a series of chloroalkenes possessing both C-Cl and C v C bonds separated by various distances, we show that the cross sections are determined by the lifetime of the lower anion state created by the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The analysis 11 showed that the LUMO resonance of allyl chloride possesses a substantially longer lifetime than that of the most stable conformer of 4-chloro-1-butene, thus accounting for its much larger DEA cross section. The source for this arises in part from a rather subtle cancellation owing to a sign difference occurring in the expression for the composite resonance width.…”
Section: Discussion Of N-chloro-1-alkenesmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis 11 showed that the LUMO resonance of allyl chloride possesses a substantially longer lifetime than that of the most stable conformer of 4-chloro-1-butene, thus accounting for its much larger DEA cross section. The source for this arises in part from a rather subtle cancellation owing to a sign difference occurring in the expression for the composite resonance width.…”
Section: Discussion Of N-chloro-1-alkenesmentioning
confidence: 99%
“…For the record, we find ratios of 1.4, 6.4, 4.8, and 1.8 for n=1-4 respectively in this comparison. 11 However, we found that it was necessary to account for the composite resonance lifetime as a function of these coefficients and their phases to successfully describe DEA in the full set of compounds that includes allyl chloride. We suggest, however, that the difference arises mainly from the much lower ‫ء‬ VAEs relative to those of the ethylenic compounds, which will give rise to longer resonance lifetimes.…”
Section: Discussion Of 1-chloro-n-phenylalkanesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, certain amino acids, including tryptophan, phenylalanine, and cysteine (Cys), have side groups that can support low energy resonances [13]. These complex, low symmetry molecules may support mixing of anionic states (i.e., mixing of the TNI state associated with an electron bound on the -COOH and -R groups) [14]. Mixing of the states may alter the energy and lifetime of the TNI compared to values associated with temporary anionic states of independent or separated functional groups.…”
Section: Introductionmentioning
confidence: 98%
“…A biological molecule with a long-lived TNI state may transfer an electron to a site that is distant from the point of attachment, inducing remote bond breaking. This type of ionization process may be the most radiologically significant for the strand breaking mechanisms of DNA [1,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%